Training of Jump Over the Bar 30 cm high with Burdened 1 kg To Eksplosion Power Leg Muscles - I Gusti Putu Ngurah Adi Santika; Maryoto Subekti (Jurnal Pendidikan Jasmani (JPJ), 2020)
The power of leg muscles plays a very important role in the sport of volleyball. Based on preliminary research conducted at Junior high school Negeri 5 Mengwi, it was found that the explosive power of volleyball extracurricular participants was still in the low category. The purpose of this study was to determine the effect of jumping a 30 cm bar with a weight of 1 kg on the explosive power of the leg muscles. The research applied was experimental research using experimental research design randomize pre and post test group design. The pure sample in the study amounted to 34 people consisting of 17 people in the control group and 17 people in the treatment group. Based on the discussion, it was found that training to jump a bar as high as 30 cm with a load of 1 kg can increase the explosive power of the leg muscles by 8.80 cm or 20.91%. So it can be concluded that training to jump a bar as high as 30 cm with a load of 1 kg can increase the explosive power of the leg muscles.